Konstruksi Keadilan Gender dalam Bingkai Pancasila dan Al-Qur’an - Himmah Aliyah; Muhammad Hariyadi (SUHUF, 2025)
This study explores gender justice within the framework of Pancasila and the Qur’an through the thoughts of Musdah Mulia and Husein Muhammad. The analysis reveals harmony between the values of humanity, brotherhood, and justice, affirming the equal status, rights, and responsibilities of women and men in social, political, and religious life. Pancasila, with its five principles, and the Qur’an, through its emphasis on monotheism and humanity, both reject gender discrimination and encourage a just society. This position contrasts with classical commentators such as Ibn Kasir, whose literal-patriarchal interpretations often subordinated women. Musdah Mulia’s feminist-humanist reading affirms gender equality as a divine imperative, while Husein Muhammad’s contextual interpretation critiques patriarchal culture and promotes women’s rights through progressive-traditional arguments. The study identifies persistent patriarchy, biased religious interpretations, and unresponsive policies as key challenges, but highlights the potential of contextual reinterpretation of Pancasila and the Qur’an to develop inclusive, gender-just policies. Employing library research, this study applies qualitative descriptive analysis, thematic interpretation, and critical hermeneutics.